Revision of the Palaearctic genus Skorikovia Ovtchinnikov, 2002 (Hymenoptera: Mutillidae) - Lelej, Arkady S. (Zootaxa, 2024)
Ten Palaearctic species of Skorikovia Ovtchinnikov, 2002 are reviewed. The new species S. bactriana sp. nov., male (Afghanistan, Tajikistan) and S. maxim sp. nov., male, female (Russia: Astrakhan Region, Kalmykia; Azerbaijan, North Iran, South-West Pakistan) are described and illustrated. A new synonymy is proposed for S. trinotata (Costa, 1858), comb. nov. (=Mutilla triangularis Radoszkowski, 1865, female, syn. nov., =Smicromyrme pliginskiji Lelej, 1984, male, syn. nov.). A lectotype of Mutilla serta Radoszkowski, 1885, female and M. triangularis Radoszkowski, 1865, female are designated. A new combination is proposed for Skorikovia serta (Radoszkowski, 1885), comb. nov. (from the genus Smicromyrme Thomson, 1870). The genus Skorikovia and S. trinotata are newly recorded from Slovakia and Austria. A key to the species of males and females and the behavior of the female of S. elongata in south-eastern Kazakhstan are provided.